2021
DOI: 10.1021/jacs.1c07757
|View full text |Cite
|
Sign up to set email alerts
|

Spectral Stable Blue-Light-Emitting Diodes via Asymmetric Organic Diamine Based Dion–Jacobson Perovskites

Abstract: The spectral instability issue is a challenge in blue perovskite light-emitting diodes (PeLEDs). Dion–Jacobson (DJ) phase perovskites are promising alternatives to achieve high-quality blue PeLEDs. However, the current exploration of DJ phase perovskites is focused on symmetric divalent cations, and the corresponding efficiency of blue PeLEDs is still inferior to that of green and red ones. In this work, we report a new type of DJ phase CsPb(Br/Cl) 3 perovskite via introduction of an asy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 56 publications
(103 reference statements)
2
37
0
Order By: Relevance
“…Similarly, several other organic ligands have been proposed for producing stable 2D DJ MHPs, such as asymmetric N,N-dimethyl-1,3-propanediamine (DPDA) and conjugated 2-fluoro-[1,1′-biphenyl]-4,4′-diyl)-dimethanaminium (FPP). 62,63 Furthermore, those ligand engineering methods intended for optimized 2D phase distribution as presented in Defect Suppression of MHPs were also proved to be favorable for enhancing the EL stability of 2D/quasi 2D PeLEDs.…”
Section: Thementioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, several other organic ligands have been proposed for producing stable 2D DJ MHPs, such as asymmetric N,N-dimethyl-1,3-propanediamine (DPDA) and conjugated 2-fluoro-[1,1′-biphenyl]-4,4′-diyl)-dimethanaminium (FPP). 62,63 Furthermore, those ligand engineering methods intended for optimized 2D phase distribution as presented in Defect Suppression of MHPs were also proved to be favorable for enhancing the EL stability of 2D/quasi 2D PeLEDs.…”
Section: Thementioning
confidence: 99%
“…Compared with commonly used PEABr, the stronger binding force between P-PDABr 2 and [PbBr 6 ] 4– octahedrons led to stable low-dimensional domains, thereby improving the spectral stability of deep-blue PeLEDs. Similarly, several other organic ligands have been proposed for producing stable 2D DJ MHPs, such as asymmetric N , N -dimethyl-1,3-propanediamine (DPDA) and conjugated 2-fluoro-[1,1′-biphenyl]-4,4′-diyl)-dimethanaminium (FPP). , Furthermore, those ligand engineering methods intended for optimized 2D phase distribution as presented in Defect Suppression of MHPs were also proved to be favorable for enhancing the EL stability of 2D/quasi 2D PeLEDs.…”
Section: Origins Of Device Degradationmentioning
confidence: 99%
“…Asymmetric geometry is comprehensively furnished in organic and perovskite optoelectronic fields (such as light‐emitting diodes, solar cells) as it can provide distinct dipole effects and 3D spatial configurations. [ 26–31 ] In this work, a novel process‐aid solid (PAS) engineering is proposed by applying asymmetric configuration on volatile solid, where a volatile 1,3‐dibromo‐5‐chlorobenzene (DBCl) solid (shown in Figure a) with asymmetric halogen around benzene ring is selected to construct the high‐performance organic solar cells. The key superiority of PAS engineering is the elevated dipole moment, unidentical dipole direction and evident interlaminar noncovalent interaction after coupling asymmetric DBCl with BTP core in Y‐series small molecule.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16][17] Although a wide emission spectral region from blue to NIR has been reported, investigations into DJ-type PeLEDs are still rare compared to RP-type ones. 12,[18][19][20][21][22][23] Qi et al used a propane-1,3-diammonium cation to fabricate blue emission devices and got an EQE of 8.5% by optimization. They also found that when they added chloride ions to tune the emission for shorter wavelength, phase segregation appeared during operation.…”
Section: Introductionmentioning
confidence: 99%
“…13–17 Although a wide emission spectral region from blue to NIR has been reported, investigations into DJ-type PeLEDs are still rare compared to RP-type ones. 12,18–23…”
Section: Introductionmentioning
confidence: 99%